Policy Adoption, Innovation, and Performance Management: The Case of Performance-funding Policies in State Postsecondary Education. (March 2019) - Birdsall, Chris
Since the 1980s, nearly every state government has implemented some form of performance management. This article turns to the context of public higher education where the use of performance management has been popular but highly controversial and unstable. Using the Cox conditional gap time model for repeating events and state-level panel data, this article investigates the factors associated with the adoption and readoption of performance-based funding policies for public higher education. Results indicate that state higher education governing structures, increases in public tuition, and educational attainment are important predictors of whether a state adopts performance-based funding.